Multiple-Dose Pharmacokinetics and Pharmacodynamics of Abacavir Alone and in Combination with Zidovudine in Human Immunodeficiency Virus-Infected Adults - McDowell, James A. (American Society for Microbiology, 2000)
Abacavir (1592U89) is a nucleoside reverse transcriptase inhibitor with potent activity against human immunodeficiency virus type 1 (HIV-1) when used alone or in combination with other antiretroviral agents. The present study was conducted to determine the multiple-dose pharmacokinetics and pharmacodynamics of abacavir in HIV-1-infected subjects following oral administration of daily doses that ranged from 600 to 1,800 mg, with and without zidovudine. Seventy-nine subjects received abacavir monotherapy for 4 weeks (200, 400, or 600 mg every 8 hours [TID] and 300 mg every 12 h [BID]) and thereafter received either zidovudine (200 mg TID or 300 mg BID) or matching placebo with abacavir for 8 additional weeks. Pharmacokinetic parameters were calculated for abacavir after administration of the first dose and at week 4 and for abacavir, zidovudine, and its glucuronide metabolite at week 12. The concentrations of abacavir in cerebrospinal fluid were determined in a subset of subjects. Steady-state plasma abacavir concentrations were achieved by week 4 of monotherapy and persisted to week 12. At steady state, abacavir pharmacokinetic parameters (area under the plasma concentration-time curve for a dosing interval [AUC(tau)] and peak concentration [C(max)]) were generally proportional to dose over the range of a 600- to 1,200-mg total daily dose. Coadministration of zidovudine with abacavir produced a small and inconsistent effect on abacavir pharmacokinetic parameters across the different doses. At the clinical abacavir dose (300 mg BID) zidovudine coadministration had no effect on the abacavir AUC(tau), which is most closely associated with efficacy. Zidovudine pharmacokinetics appeared to be unaffected by abacavir. Statistically significant but weak relationships were found for the change in the log(10) HIV-1 RNA load from the baseline to week 4 versus total daily AUC(tau) and C(tau) (P < 0.05). The incidence of nausea was significantly associated with total daily AUC(tau) and C(max). In conclusion, abacavir has predictable pharmacokinetic characteristics following the administration of multiple doses.